Mackerel Tuna Fortification for Improving Wet Noodle Quality - Holinesti, Rahmi; Faridah, Anni; Gusnita, Wiwik; Insan, Ranggi Rahimul; Mustika, Sari; Utami, Riski Gusri; Gusri, Serina (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
Wet noodles are raw noodles that, before being marketed, undergo a boiling process in boiling water, with a water content of around 35%, and after boiling, the water content increases to 52%. In general, wet noodles are only made from the essential ingredients of wheat flour and eggs, with a protein content of 11.852%. This figure is low for one serving of food per human day. Therefore, it is necessary to think about alternative materials that can be used to increase the protein content of wet noodles. One of them is mackerel tuna. This study aims to describe the quality of wet noodles by adding mackerel tuna meat (10%) in terms of color, aroma, texture, and taste. The type of this research was an experiment conducted in October 2022 at the Culinary Study Program, Department of Home Economics, Faculty of Tourism and Hospitality, Universitas Negeri Padang. Data collection was carried out through organoleptic tests, which involved three expert panelists. The organoleptic test showed that the quality of wet noodles with the addition of mackerel tuna meat was light yellow, had a fragrant aroma, was chewy in texture, and had a savory mackerel tuna meat taste.